Association between Chronic Interstitial Cystitis and Herpes Zoster - Hsu, Chao-Yu (Int J Environ Res Public Health, 2020)
Objectives: Herpes zoster (HZ) infection has been associated with disease burdens such as infection and depression. However, the relationship between chronic interstitial cystitis (CIC) and HZ is unknown. This study investigated HZ risk in patients with CIC. Patients and Methods: The Longitudinal Health Insurance Database, which is a subset of the Taiwan National Health Insurance Research Database, was used in the study. The case cohort consisted of patients with newly diagnosed CIC between 2000 and 2012. Each patient with CIC was matched to four controls by age and index year. All participants were traced from the index date to HZ diagnosis, and loss to follow-up or death, or to the end of the study (31 December 2013). Results: A total of 1096 patients with CIC and 4384 controls were enrolled. The incidence rate of HZ in patients with CIC was 10.8 per 1000 person-years, whereas that for controls was 7.25 per 1000 person-years. HZ risk for the case cohort was 1.48 times that for the control cohort. Among participants aged ≤49 years, patients with CIC had a 1.91-fold-increased HZ risk compared to those without CIC. Conclusion: Patients with CIC had a higher risk of HZ than those without CIC. CIC should not be ignored, particularly in young adults.